2010
DOI: 10.1097/coc.0b013e31819fdf5e
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Plitidepsin 3-Hour Infusion Every 2 Weeks in Patients With Unresectable Advanced Medullary Thyroid Carcinoma

Abstract: Single-agent plitidepsin given as 3-hour i.v. infusions every 2 weeks was generally well tolerated but showed limited clinical activity in patients with unresectable advanced MTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 28 publications
0
10
0
2
Order By: Relevance
“…Results from other malignancies comprised: two PRs and one SD among 19 patients with unresectable advanced renal cell carcinoma, with a 2.1-month progression-free interval (PFI) (APL-B-001-01);41 11 SDs out of 16 patients with unresectable advanced medullary thyroid carcinoma, with a clinical benefit noted in only one patient (APL-B-002-02);42 three SDs in 17 patients with locally advanced or metastatic non-small-cell lung cancer, with a TTP of 1.2 months (APL-B-004-02);43 no responses in another trial of 19 patients with small-cell lung cancer pretreated with one line (APL-B-006-02);44 one SD as second-line therapy for 18 patients with advanced or metastatic transitional cell carcinoma of the urothelium (APL-B-005-02),45 two SDs among 22 assessable patients with advanced dedifferentiated liposarcomas, with a median PFS of 1.6 months (APIPLO study) 46. Coadministration of L-carnitine did not increase treatment efficacy and did not prevent the muscular toxicity or CPK-elevation associated with plitidepsin in patients with unresectable advanced renal cell carcinoma 41…”
Section: Developmentmentioning
confidence: 99%
“…Results from other malignancies comprised: two PRs and one SD among 19 patients with unresectable advanced renal cell carcinoma, with a 2.1-month progression-free interval (PFI) (APL-B-001-01);41 11 SDs out of 16 patients with unresectable advanced medullary thyroid carcinoma, with a clinical benefit noted in only one patient (APL-B-002-02);42 three SDs in 17 patients with locally advanced or metastatic non-small-cell lung cancer, with a TTP of 1.2 months (APL-B-004-02);43 no responses in another trial of 19 patients with small-cell lung cancer pretreated with one line (APL-B-006-02);44 one SD as second-line therapy for 18 patients with advanced or metastatic transitional cell carcinoma of the urothelium (APL-B-005-02),45 two SDs among 22 assessable patients with advanced dedifferentiated liposarcomas, with a median PFS of 1.6 months (APIPLO study) 46. Coadministration of L-carnitine did not increase treatment efficacy and did not prevent the muscular toxicity or CPK-elevation associated with plitidepsin in patients with unresectable advanced renal cell carcinoma 41…”
Section: Developmentmentioning
confidence: 99%
“…Although QoL is reported in NET studies, the lack of standardisation of measurement tools between studies and the non-NET-specific nature of the tools used made comparing and generalising findings difficult. Table 4 provides a summary of the tools used to assess QoL in patients with NET (Aaronson et al 1993;O'Toole et al 2000;Larsson et al 2001Larsson et al , 2003Larsson et al , 2007Davies et al 2003Davies et al , 2006Major et al 2003;Pasieka et al 2004;Teunissen et al 2004;Frojd et al 2007Frojd et al , 2009Haugland et al 2009;Korse et al 2009;Muros et al 2009;Pezzilli et al 2009;Vinik et al 2009Vinik et al , 2011Baudin et al 2010;Beaumont et al 2010Beaumont et al , 2012. Our review showed that a variety of tools was used in patients with NET to assess disease-or treatmentrelated HRQoL and to evaluate global QoL, functioning, symptoms and mental well-being domains.…”
Section: Quality Of Lifementioning
confidence: 95%
“…Later, similarly, weekly single‐agent plitidepsin at a dose of 3.2 mg/m 2 as second‐lined therapy showed no antitumor activity in treating patients with relapsed small‐cell lung cancer (PFS: 1.3 months; median OS: 4.8 months) . The same activity was seen in metastatic transitional cell carcinoma of the bladder with 1.4 months and 2.3 months in terms of PFS and OS, respectively , in unresectable advanced medullary thyroid carcinoma , and recently in liposarcoma (median PFS: 1.6 months; OS: 9.2 months) . As yet, a minor clinical response was seen with biweekly plitidepsin at a dose of 5 mg/m 2 in advanced melanoma (median PFS: 1.3 months; median OS: 3.5 months) .…”
Section: Targeting the Tumor Vasculature By Natural Compounds: Perspementioning
confidence: 98%